RELATIONSHIP BETWEEN CERVICAL DILATATION AT WHICH WOMEN PRESENT IN LABOR AND SUBSEQUENT RATE OF CAESARIAN SECTION - Anjum, Naureen; Memon, Zaibunissa; Sheikh, Sana; Naz, Urooj (Journal of Ayub Medical College Abbottabad, 2020)
Background: Increasing rate of caesarean section is becoming an epidemic worldwide. This study was conducted to compare rate of caesarean section between women presenting in labor with cervical dilatation less than 4 cm to those with cervical dilatation 4 cm or more. Methods: This study was conducted at Aga Khan Hospital for Women, Karimabad. Women with singleton pregnancy and cephalic presentation at term in spontaneous labour were included. Patients were divided in two groups: early presenters with cervical dilatation less than 4 cm and late presenters with cervical dilatation of 4 cm or more. Primary outcome measured was rate of caesarean section, while secondary outcomes were duration of labour, APGAR score and any neonatal complication. Results: Medical records of 442 women were reviewed. Difference in mean age of women presenting early in labour was of 2 years (26.8±4.7 vs 28.4±4.5) which was significant (p-value 0.01). More than two thirds of primiparas presented early (69.0% vs 31%) in labour and early presenters had longer labour (p-value <0.001). 62% of early presenters had artificial rupture of membrane compared to 41% of late presenters and nearly 73% required analgesia (p-value <0.001). Caesarean section rate was 10.5% in early and 1.8% in late presenters that was significant (p-value <0.001). APGAR score of both groups was comparable. Conclusion: Integrated midwifery services and antenatal classes may help in education of labouring women and their understanding of labour process and so that low risk women can be monitored at home and come to hospital in active labour. Keywords: Caesarean section; Cervical dilatation; Spontaneous labor